The Czech Language in Volhynia A. Arkhanhelska, O. Bláha, U. Cholodová (eds.): Čeština na Volyni. 2020. Olomouc. Univerzita Palackého v Olomouci. ISBN 978-80-88278-62-7 - Henzelmann, Martin (Slavica, 2022)
In 2020, a collective monograph was published in Olomouc dedicated to the nature of the Czech language and culture in Volhynia in today’s Ukraine, overviewing the settlement and history of Czech migrants in this area, including culture-specific features of the local Czech identity, especially in the late 19th and early 20th centuries. Language features, which play a significant role,are also described. The volume sheds light on phenomena of language contact, in subsystems such as phonetics and phonology, morphosyntax, and lexicology. In this context, the authors present and analyze empirical material. The book is an important contribution to the study of Czech cultural heritage outside the country’s borders.